Membangun Kemandirian: Peran Masyarakat Dalam Mengatasi Tantangan SDGS - Hadinugroho, Aulya Robby; Nugraheni, Nursiwi (Yayasan Daarul Huda Kruengmane, 2024)
Local entrepreneurship training programs are an important instrument in efforts to increase the economic and social independence of communities and achieve Sustainable Development Goals (SDGs). This research aims to explore the role and implications of entrepreneurship training programs in the context of achieving sustainable development goals. The research method used is a literature study to analyze various relevant sources about entrepreneurship training programs and their impact on the SDGs. Local entrepreneurship training programs have positive implications for achieving SDGs, especially in alleviating poverty (SDGs 1), improving community welfare (SDGs 3), and economic empowerment (SDGs 8). Through BUMDes support, this program can make a significant contribution to sustainable development at the local level.